AHP-SAW and AHP-WP Sensitivity Test in DSS Design For Housing Location Selection - Wahyudi, Adhie Tri; Suparti, Erni; Waruju, Resmitha Dian (Jurnal Aplikasi Ilmu Teknik Industri (JAPTI), 2022)
The Decision Support System (DSS) is implemented by CV. IKS assists the director as a Decision Maker in determining the location of housing developments. In the case of determining the location of the subsidized housing project that was carried out in 2020, the DSS developed with two methods, namely DSS1 with the AHP – WP method and DSS2 with the AHP – SAW method, gives different outputs. The purpose of this paper is to conduct a sensitivity test to determine the MADM method most suitable for completing the locating determination of subsidized housing projects in CV. IKS. The sensitivity test method was chosen because this method can detect every ranking change in each MADM method. The more sensitive the value obtained from the change in ranking suggests the MADM method is the best in displaying the order of the ranked alternatives. It can be seen from the sensitivity test results that the change value of the AHP-WP method is 3.178%, and the change value of the AHP-SAW method is -19.274%. It concluded that the AHP-WP method was considered to be the most relevant in addressing the problem of determining the location of housing developments in the CV. IKS.Keywords: sensitivity test, MADM, AHP-SAW method, AHP-WP method, housing location determination